Korona dalam Ruang Politik dan Poetik Sastra: Arena Diskursif Karya-karya Fiksi Komunitas Jejak Imaji Yogyakarta Di Era Pandemi - Sudibyo, Sudibyo; Dewojati, Cahyaningrum; Indrastuti, Novi Siti Kussuji; Zuliana, Rina (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2021)
This article departs from the findings of the implementation of the community service program of Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada in the form of providing workshop and assistance in writing fiction works for the Komunitas Jejak Imaji (KJI). KJI is a space of community for writers, poets, and students who carry out the routine of gathering, discussing, and producing literary works. This community is located in Yogyakarta — which culturally has a social climate that supports the existence of literary development and the literary community. In the midst of a pandemic, the demands for innovation on the formation of new habits and new knowledge provide a new field for communities to continue to exist in producing literary works. This service was initiated to spark community awareness to revive its literary space amid the pandemic. The implementation of the service program uses lecture, discussion, and practice methods to produce works about Covid-19 that are ready to be published through the application of research and processing of historical data, as well as social facts in literary works. Even though the story ideas from the 14 works of fiction they wrote were a response to the Covid-19 pandemic, the tendency of their works is not far from the social problems surrounding them. The conceptual framework used to see the tendency of KJI's fiction is Laclau and Mouffe's discourse theory which is to answer the question of how the corona is received and responded to in a political space as well as a literary poetic space. The results of these activities show that the entire works of fiction written by the Imaji Literature Community, tend to put the discourse of globality clashed with various social problems experienced by the Indonesian people in general and local communities in particular during the pandemic. ===== Tulisan ini berangkat dari temuan pelaksanaan program pengabdian kepada masyarakat Magister Sastra, Fakultas Ilmu Budaya, Universitas Gadjah Mada berupa pemberian pelatihan (workshop) dan pendampingan penulisan karya fiksi untuk Komunitas Jejak Imaji (KJI). KJI merupakan salah satu ruang sastrawan, penyair, dan mahasiswa yang ‘menggemari sastra’ melaksanakan rutinitas berkumpul, berdiskusi, dan memproduksi karya sastra. Komunitas ini berlokasi di Yogyakarta—yang secara kultural memiliki iklim pergaulan yang mendukung eksistensi perkembangan sastra dan komunitas sastra di dalamnya. Di tengah pandemi, tuntutan inovasi atas terbentuknya kebiasaan baru dan pengetahuan baru memberikan medan baru bagi komunitas untuk tetap eksis dalam memproduksi karya sastra. Pengabdian ini diinisiasi untuk memantik kesadaran komunitas untuk menghidupi ruang sastranya kembali di tengah pandemi. Pelaksanaan program pengabdian menggunakan metode ceramah, diskusi, dan praktik hingga menghasilkan karya tentang covid-19 yang siap publis melalui penerapan riset dan pengolahan data sejarah, serta fakta sosial dalam karya sastra. Meskipun ide cerita dari 14 karya fiksi yang mereka tulis merupakan respon atas pandemi covid-19, kecenderungan karya-karya mereka tidak jauh dari persoalan sosial di sekitarnya. Kerangka konseptual yang digunakan untuk melihat kecenderungan karya fiksi KJI adalah konsepsi wacana Laclau dan Mouffe yang untuk menjawab pertanyaan bagaimana korona diterima dan direspon dalam ruang politik sekaligus ruang poetik sastra. Dari hasil kegiatan tersebut menunjukkan bahwa keseluruhan karya fiksi yang ditulis oleh Komunitas Sastra Jejak Imaji cenderung meletakkan wacana global yang dibenturkan dengan berbagai persoalan sosial yang dialami masyarakat Indonesia pada umumnya dan masyarakat lokal pada khususnya selama pandemi.